Wits Libraries - Research Visibility and Open Scholarship - Mphuti, Bongi (University of the Witwatersrand, Johannesburg, 2025)
Abstract not available
A presentation presented during KWANZA Tanzania/Uganda RDM Training session, at Open Library Area (OLA), Wartenweiler Library, on the 07 August 2025.
Keywords: Research Visibility and Open Scholarship; Kwanza; Tanzania; Uganda; Wits Institutional Repository (WIReDSpace); Wits Open Data Vault (WODV); Open Access Publishing; Copyright and FAIR Use; Research; Open Scholarship and User Experience; Global Impact Analytics; Sustainable Development Goals (SDGs); Impactful Research Outputs; Wits Research Data Management (RDM); Wits Research Data Management (RDM) Policy; Impact of Datasets; Wits Libraries; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure